Social Media Representations of Law Enforcement within Four Diverse Chicago Neighborhoods. (December 2020) - Sodhi, Aparna; Aguilar, Nathan; Choma, Deanna E; Steve, Jackie Marie; Patton, Desmond; Crandall, Marie
The perception of excessive use of force by law enforcement towards minorities has become an increasing focus of attention in the national media and public consciousness. With greater ability to record conflicts using smartphones and dissemination of videos via social media, the public may more readily judge the circumstances of law enforcement interactions. The purpose of this study was (a) to understand the general sentiment about law enforcement on social media among communities of color in Chicago, (b) to see if local or national incidents of police conflicts with people of color were mentioned, and (c) identify key themes within these social media posts. Publicly available social media posts were collected from four ethnically and socioeconomically diverse neighborhoods in Chicago. Using a five-person team and keyword searches, the posts were reviewed for content and abstracted if they pertained to law enforcement. They were then analyzed in stages of open, axial, and selective coding methods. Eight main themes were identified. These included the following: (a) law enforcement participation in the community, (b) law enforcement activity in the neighborhood, (c) posts regarding criminal activity, (d) immigration, (e) political protests against police, (f) African American men and law enforcement, (g) sympathy with Sandra Bland case, and (h) #Blacklivesmatter. There appears to be chasm of trust between law enforcement and communities of color. Our findings may help inform law enforcement, public policy-makers, and social workers in their efforts to better address these issues and to institute policies and interventions that not only bridge this gap but also strengthen and empower these communities.